Meso-substituted porphyrin photosensitizers with enhanced near-infrared absorption: Synthesis, characterization and biological evaluation for photodynamic therapy. Issue 21 (24th May 2018) - Pan, Dong; Zhong, Xiangmin; Zhao, Weidong; Yu, Zhaofeng; Yang, Zhou; Wang, Dong; Cao, Hui; He, Wanli
Abstract: Porphyrin derivatives are widely explored and used in photodynamic therapy, for their marvelous therapeutic properties. In order to fill in the gaps of insufficient photosensitizers with near-infrared absorption, three porphyrin molecules, 5, 10, 15, 20-tetrakis(3, 4-bis(2-(-2-(2-hydroxyethoxy)ethoxy)ethoxy)benzyl)zinc porphyrin(P1), 5, 15-bis(3, 4-bis(2-(-2-(2-hydroxyethoxy)ethoxy)ethoxy)benzyl)-10, 20-bis(2-(2-(2-(4-ethynylphenoxy)ethoxy)ethoxy)ethanol)zincporphyrin(P2), 5, 15-bis(3, 4-bis(2-(-2-(2-hydroxyethoxy)ethoxy)ethoxy)benzyl)-10, 20-N, N-dibutyl-4-ethynylaniline zinc porphyrin(P3), were designed and synthesized targeting for more efficient cancer treatment. Excellent photophysical properties were illustrated by UV–vis absorption and emission spectra with enhanced absorbance between 650 and 750 nm and fluorescence emission within 600–800 nm. Besides, with high 1 O2 quantum yield, especially P2 (0.89), all porphyrins were further evaluated in vitro by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay against Hela cells and exhibited negligible dark toxicity and robust phototoxicity. Fluorescence confocal laser microscopy confirmed cellular uptake and diffusion of these porphyrins, therefore demonstrated their potential and promising applications in photodynamic therapy. Graphical abstract: